Phonological Variations Are Compensated at the Lexical Level: Evidence From Auditory Neural Activity - Zora, Hatice; Riad, Tomas; Ylinen, Sari; Csépe, Valéria (Frontiers in Human Neuroscience, 2021)
Dealing with phonological variations is important for speech processing. This article addresses whether phonological variations introduced by assimilatory processes are compensated for at the pre-lexical or lexical level, and whether the nature of variation and the phonological context influence this process. To this end, Swedish nasal regressive place assimilation was investigated using the mismatch negativity (MMN) component. In nasal regressive assimilation, the coronal nasal assimilates to the place of articulation of a following segment, most clearly with a velar or labial place of articulation, as in utan mej ‘without me’ > [ʉːtam mɛjː]. In a passive auditory oddball paradigm, 15 Swedish speakers were presented with Swedish phrases with attested and unattested phonological variations and contexts for nasal assimilation. Attested variations – a coronal-to-labial change as in utan ‘without’ > [ʉːtam] – were contrasted with unattested variations – a labial-to-coronal change as in utom ‘except’ > *[ʉːtɔn] – in appropriate and inappropriate contexts created by mej ‘me’ [mɛjː] and dej ‘you’ [dɛjː]. Given that the MMN amplitude depends on the degree of variation between two stimuli, the MMN responses were expected to indicate to what extent the distance between variants was tolerated by the perceptual system. Since the MMN response reflects not only low-level acoustic processing but also higher-level linguistic processes, the results were predicted to indicate whether listeners process assimilation at the pre-lexical and lexical levels. The results indicated no significant interactions across variations, suggesting that variations in phonological forms do not incur any cost in lexical retrieval; hence such variation is compensated for at the lexical level. However, since the MMN response reached significance only for a labial-to-coronal change in a labial context and for a coronal-to-labial change in a coronal context, the compensation might have been influenced by the nature of variation and the phonological context. It is therefore concluded that while assimilation is compensated for at the lexical level, there is also some influence from pre-lexical processing. The present results reveal not only signal-based perception of phonological units, but also higher-level lexical processing, and are thus able to reconcile the bottom-up and top-down models of speech processing.